Goazen mendira! (Let`s go to the mountains!). Hill walking and Basque identity - Mirgos, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to discuss the ideological function of mountain landscape in the Basque nationalism and the importance of sport, especially mountain sports and activities, in the process of creating, reproducing and transmitting Basque identity. It includes an outline of the history of the Basque presence in the mountains, as well as the political dimension of hiking in the mountains and conquering mountain peaks.
Keywords: sport; Basque Country; identity; mountain; landscape; ideology